2006
DOI: 10.1016/j.chembiol.2005.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Mining for Aspergillus Natural Products

Abstract: The genus Aspergillus is renowned for its ability to produce a myriad of bioactive secondary metabolites. Although the propensity of biosynthetic genes to form contiguous clusters greatly facilitates assignment of putative secondary metabolite genes in the completed Aspergillus genomes, such analysis cannot predict gene expression and, ultimately, product formation. To circumvent this deficiency, we have examined Aspergillus nidulans microarrays for expressed secondary metabolite gene clusters by using the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
297
3
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(315 citation statements)
references
References 26 publications
10
297
3
5
Order By: Relevance
“…In yeast, Yap proteins often exhibit overlapping roles, so we reasoned that other A. nidulans Yap-like bZIPs would also affect SM. We examined this possibility by characterizing four other bZIP proteins that bore residues conserved with respect to RsmA/ Yap proteins (as assessed by CLUSTAL W analysis) in the DNA binding motif and also showed differential expression in microarray profiles of laeA mutants (Bok et al, 2006; data not shown). These proteins included the already characterized NapA (AN7513) , as well as three uncharacterized proteins (AN11891, AN8772 and AN10378, hereinafter called ZipA, ZipB and ZipC).…”
Section: Selection Of Bzipsmentioning
confidence: 99%
“…In yeast, Yap proteins often exhibit overlapping roles, so we reasoned that other A. nidulans Yap-like bZIPs would also affect SM. We examined this possibility by characterizing four other bZIP proteins that bore residues conserved with respect to RsmA/ Yap proteins (as assessed by CLUSTAL W analysis) in the DNA binding motif and also showed differential expression in microarray profiles of laeA mutants (Bok et al, 2006; data not shown). These proteins included the already characterized NapA (AN7513) , as well as three uncharacterized proteins (AN11891, AN8772 and AN10378, hereinafter called ZipA, ZipB and ZipC).…”
Section: Selection Of Bzipsmentioning
confidence: 99%
“…2). The fact that we can map expression for 58 of the 70 biosynthetic genes (a large proportion of the gene clusters) is surprising, considering that many, or even the majority, of the gene clusters are reported to be silent under standard laboratory conditions (13,14,20,(36)(37)(38). An example of a cluster previously described as silent but identified here is the inpAB cluster (39).…”
mentioning
confidence: 99%
“…In Aspergillus, the interaction between VeA and LaeA, a protein methyltransferase, regulates transcription of genes within clusters involved in SM synthesis. Researchers have hypothesized that LaeA is involved in chromatin remodeling through histone methylation (2,4,10). The diminished FB production by F. verticillioides strains lacking FvVE1 suggests that the expression of genes in the FUM cluster is regulated not only at the level of the individual inducible promoters, but also epigenetically.…”
mentioning
confidence: 99%